Grafting Watermelon Onto Pumpkin Increases Chilling Tolerance by Up Regulating Arginine Decarboxylase to Increase Putrescine Biosynthesis - Lu, Junyang; Cheng, Fei; Huang, Yuan; Bie, Zhilong (Frontiers in Plant Science, 2022)
Low temperature is a major environmental factor that severely impairs plant growth and productivity. Watermelon (Citrullus lanatus) is a chilling-sensitive crop. Grafting of watermelon onto pumpkin rootstock is an effective technique to increase the chilling tolerance of watermelon when exposure to short-time chilling stress. However, the mechanism by which pumpkin rootstock increases chilling tolerance remains poorly understood. Under 10 °C/5 °C (day/night) chilling stress treatment, pumpkin-grafted watermelon seedlings showed higher chilling tolerance than self-grafted watermelon plants with significantly reduced lipid peroxidation and chilling index. Physiological analysis revealed that pumpkin rootstock grafting led to the notable accumulation of putrescine in watermelon seedlings under chilling conditions. Pre-treat foliar with 1 mM D-arginine (inhibitor of arginine decarboxylase, ADC) increased the electrolyte leakage (EL) of pumpkin-grafted watermelon leaves under chilling stress. This result can be ascribed to the decrease in transcript levels of ADC, ornithine decarboxylase, spermidine synthase, and polyamine oxidase genes involved in the synthesis and metabolism of polyamines. Transcriptome analysis showed that pumpkin rootstock improved chilling tolerance in watermelon seedlings by regulating differential gene expression under chilling stress. Pumpkin-grafted seedling reduced the number and expression level of differential genes in watermelon scion under chilling stress. It specifically increased the up-regulated expression of ADC (Cla97C11G210580), a key gene in the polyamine metabolism pathway, and ultimately promoted the accumulation of putrescine. In conclusion, pumpkin rootstock grafting increased the chilling tolerance of watermelon through transcription adjustments, up regulating the expression level of ADC, and promoting the synthesis of putrescine, which ultimately improved the chilling tolerance of pumpkin-grafted watermelon plants.